2023
DOI: 10.3389/fmicb.2023.1130226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of HPV infection among women in Xiamen, China

Abstract: ObjectiveThis study aimed to evaluate the prevalence of HPV and genotype distribution among female populations in Xiamen, Fujian Province, China, which can be conducive for local governments to formulate cervical cancer screening and HPV vaccine strategies.MethodsCervical swabs were collected from 47,926 participants aged 16–92 years at the Women and Children’s Hospital, Xiamen University, from November 2019 to June 2020. HPV DNA was extracted and detected using conventional PCR, followed by HPV subtype-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This phenomenon can be attributed to the fact that our study included a hospital-based population, whereby women may have exhibited symptoms of genital diseases and consequently had a higher risk of HPV prevalence compared to healthy women [ 14 ]. While the HPV infection rate may vary geographically across different regions in China [ 15 17 ], the HR-HPV prevalence in our study was similar to that reported in other hospital-based studies conducted in China (21.62% vs 21.07%) [ 18 , 19 ].Several factors, such as economic levels, living habits, and knowledge levels, may contribute to the slight variation observed. It is widely accepted that a majority of HPV infections and associated cancers occur in economically disadvantaged areas [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…This phenomenon can be attributed to the fact that our study included a hospital-based population, whereby women may have exhibited symptoms of genital diseases and consequently had a higher risk of HPV prevalence compared to healthy women [ 14 ]. While the HPV infection rate may vary geographically across different regions in China [ 15 17 ], the HR-HPV prevalence in our study was similar to that reported in other hospital-based studies conducted in China (21.62% vs 21.07%) [ 18 , 19 ].Several factors, such as economic levels, living habits, and knowledge levels, may contribute to the slight variation observed. It is widely accepted that a majority of HPV infections and associated cancers occur in economically disadvantaged areas [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“… 32 , 33 Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population. 9 , 29 , 34 , 35 , 36 , 37 , 38 In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51. We further evaluated HPV genotype distribution stratified by pathology grade as a proxy for risk assessment to identify genotypes that warrant distinct management.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies carried out in different geographical areas, mainly in China, have shown similar results. HPV51 has been reported in several studies to be one of the most common circulating genotypes in women, similar to HPV53 and HPV68 [ 52 , 53 , 54 , 55 , 56 ]. As for HPV66, Zheng et al also identified it among the significantly prevalent hrHPV in Chinese women [ 57 ].…”
Section: Discussionmentioning
confidence: 99%